Does Mental Distress Predict Cardiac Surgical Outcome? - Buschmann, Katja; Wiltink, Jörg; Ghazy, Ahmed; Bremerich, Dorothee; Emrich, Anna Lena; Beutel, Manfred E.; Treede, Hendrik (The Thoracic and Cardiovascular Surgeon, 2022)
Mental distress is suspected to influence the morbidity of cardiac patients. Evaluating mental distress in cardiac patients is rare and the impact on surgical outcome is still not certified.In 94 cardiac surgical patients, mental distress was assessed by the Patient Health Questionnaire-4 (PHQ-4). We defined length of stay in hospital and on intensive care unit as well as time of mechanical ventilation as outcomes on surgery. Age, physical activity, diabetes, overweight, PHQ-4, and an inflammation marker were tested for their predictive value on outcomes.Reportedly prevalence of generalized anxiety was 16.0% and depression rate was 13.8%. Length of stay in hospital was 13 ± 8 days, time of mechanical ventilation was 10 (0–1,207) hours, and length of stay on intensive care unit was 3 ± 6 days. Length of stay in hospital was significantly predicted by age (p = 0.048), low physical activity (p = 0.029), and high C-reactive protein (CRP; p = 0.031). Furthermore, CRP was the only significant predictor of time of mechanical ventilation and length of stay on intensive care unit.Outcome was not predicted by mental distress. However, inflammation marker CRP was predictive for outcome, potentially caused by higher cardiovascular risk profile. Additionally, depression was referred to be associated with inflammation. Probably, the small sample and the timing of assessment were responsible for the missing relation between mental distress and outcome. We presume a relation with low physical activity and depression. Nevertheless, further randomized studies are needed to pay more attention on patients' distress to intervene preoperatively to improve postoperative outcome.
Keywords: outcomes (include mortality; morbidity); inflammation; systemic; neurocognitive deficits